Glucose Insulin Ratio in Hyper Insulinemic Women with Polycystic Ovarian Syndrome - Roohi Jabbar; Maria Hameed; Saima Tabassum; Saboohi Saeed; Tabinda Kazmi; Shazia Rashid (Shalamar Medical & Dental College, Lahore, Pakistan, 2022)
Background: Women with polycystic ovarian syndrome (PCOS) have insulin resistance and hyperinsulinemia that may play a key role in the pathogenesis of PCOS. Objectives: To determine and compare glucose-insulin ratio in hyper-insulinemic women with the polycystic ovarian syndrome and healthy controls. Materials & Methods: A cross-sectional comparative study was conducted at Lahore General Hospital. A total of 80 women 24-35 years of age were recruited from Lahore General Hospital. 50 women had PCOS, and 30 were healthy controls. PCOS was diagnosed by using the Rotterdam criteria. Height, weight, and waist circumference were measured. Glucose and insulin were estimated by the glucose oxidase method and ELISA, respectively. HOMA-IR was calculated to determine insulin resistance (IR). HOMA- β was calculated to assess the β-cell function. Fasting glucose and insulin ratio were also calculated. Results: Mean age of the women with PCOS and healthy controls was 29.89±3.54 and 28.60±1.12 years, respectively (p>0.54). BMI and waist circumference of women with PCOS were higher compared to healthy controls (p>0.45). Fasting glucose, fasting insulin, HOMA- β, and IR were significantly higher in women with PCOS compared to healthy controls (p<0.001). Conclusion: In addition to HOMA IR, the glucose-insulin ratio may be considered to assess hyperinsulinemia in women with polycystic ovary syndrome.